The Effects of The Corona Pandemic on Urban Planning and The Future of Yemeni Cities: A Case Study of Thamar - Al Shareem, Khaled; Yafa'a, Ahmed (Journal of Palestine Ahliya University for Research and Studies, 2024)
This study aims to explore the effects of the coronavirus pandemic on urban planning and the future of Yemeni cities, focusing on the factors that make cities more vulnerable to the spread of the virus, such as population density and social interactions. The study also discussed the measures taken by cities to mitigate the impact of the pandemic, reviewed the experiences of some countries in the post-pandemic phase, and conducted a case study in the Yemeni city of Thamar and its impact on the Coronavirus and its visions for future urban planning. The study used the inductive approach and the analytical approach, given the nature of the study and its suitability to explore and understand complex phenomena related to the Corona pandemic and urban planning. The Corona pandemic revealed the crucial role of urban planning in confronting health crises, in general, and the pandemic contributed to the necessity of rethinking the modern human lifestyle and well-being. The COVID-19 crisis has provided an excellent opportunity for planners and policymakers to take transformative action towards creating more just, resilient, and sustainable cities and the need to expand pedestrian areas, create safe green areas, provide public open spaces within cities, and provide residential neighborhoods with green, recreational spaces and parks available to all. This study highlights the importance of urban planning in light of health crises. It provides insights on enhancing the resilience of cities in general and Yemeni cities in particular and their sustainability in the future.